Organic matter sources and size structuring in stream invertebrate food webs across a tropical to temperate gradient. (21st March 2014) - Jardine, Timothy D.
Summary Given large differences in species diversity across latitudinal gradients, it has been suggested that certain structural and functional attributes of fresh waters may differ over a latitudinal range, an important consideration for poorly known tropical systems undergoing major changes caused by human activities. Two key features of aquatic ecosystems, the contribution of in situ production (periphyton) to community biomass and size structuring (individual body size versus trophic position), were measured in stream invertebrate food webs across a gradient of 15 degrees of latitude in Australia from the wet tropics to a temperate island. Consistent with earlier work, crustaceans (Atyidae and Palaemonidae) were responsible for a large fraction of the community biomass at tropical and subtropical sites. Periphyton supported a large proportion of the biomass at intermediate latitudes (79% in the subtropics and 95% at temperate mainland sites), with lower contributions both in more northerly (51% in the tropics) and more southerly (31% on a temperate island) sites. These lower contributions were driven by the high biomass of large crustaceans in the tropics and by shredding and filtering insects on the temperate island and may have also been the result of local nutrient‐limitation. Although these taxonomic differences between regions did not translate into a latitudinal gradient in size structure, the larger individual body size of crustaceans compared with insects at a given trophic position suggests that the distribution of biomass in tropical and temperate food webs will differ, with implications for predators near the top of the web. These results suggest that differences in species composition do not necessarily entail differences in stream food‐web structure and function and that local environmental factors are likely to be as important as broad‐scale biogeography and climate in driving food‐web patterns.